2004
DOI: 10.1080/0034676042000253927
|View full text |Cite
|
Sign up to set email alerts
|

You Are What You Eat: The Social Economy of the Slow Food Movement

Abstract: Recent work by Schor revives concerns raised by Veblen and Hirsch over the destructive consequences of competitive consumption. In contrast, Twitchell argues that increased access to commodities as symbols of luxury signals a democratization of class and social status. Rather than playing the role of dupes, consumers are active co-conspirators in the creation and maintenance of luxury goods markets. While flawed, each of these perspectives has something important to offer to social economists interested in und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(76 citation statements)
references
References 22 publications
0
68
0
8
Order By: Relevance
“…"Slow, then involves notions of unadulterated, locally based products, cooked in conventional ways and enjoyed at a leisurely pace in which social relations can be developed and reproduced. Read descriptions of this 'slowness' closely and it is not difficult to discern the patriarchal lens through which it is conceived, yet there are few gender-based critiques of the Slow Food movement (but see Bock 2004). social relations that underpin production and livelihoods in rural areas (Leitch 2000, Labelle 2004, Pietrykowski 2004). …”
Section: Slow Food and The Articulation Of Consumption And Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Slow, then involves notions of unadulterated, locally based products, cooked in conventional ways and enjoyed at a leisurely pace in which social relations can be developed and reproduced. Read descriptions of this 'slowness' closely and it is not difficult to discern the patriarchal lens through which it is conceived, yet there are few gender-based critiques of the Slow Food movement (but see Bock 2004). social relations that underpin production and livelihoods in rural areas (Leitch 2000, Labelle 2004, Pietrykowski 2004). …”
Section: Slow Food and The Articulation Of Consumption And Productionmentioning
confidence: 99%
“…The Ark of Taste was envisioned as "a way to catalogue animal breeds, cheeses, meats, fruits, grains, and herbs threatened with extinction due to consumer substitution with lower priced, standardized products." and is designed as a vehicle through which threatened production systems and products can be protected and extended (Pietrykowski 2004;315).…”
Section: Convivia Are Chapters Of Slowmentioning
confidence: 99%
“…Este tipo de agricultura urbana tem sido principalmente um subproduto da industrialização das áreas metropolitanas de Lisboa desde os anos 60, envolvendo populações tipicamente imigrantes de origens diferentes com fundo rural. Não foi só até a administração municipal eleita de 2007 que a agricultura urbana foi colocada na agenda política, aproveitando o ímpeto dos movimentos sociais globais, nomeadamente para melhorar a segurança alimentar, a segurança alimentar ou o movimento "slowfood", por exemplo (PIETRYKOWSKI, 2004). Em Portugal, desde 1999, cada Plano Diretor Municipal tem de circunscrever a Estrutura Ecológica Urbana para Lisboa.…”
Section: Perspectivas De Lisboa: Agricultura Urbana Em Transiçãounclassified
“…Pertinent to the Global Studio, De Wever et al (2010, p, 355) argue peer tutoring can also be seen to occur in an online environment where it improves students' "knowledge construction". Specifically pertinent to both Global Studio projects to be outlined here, cross-institutional educational endeavours conducted through ICT have been argued to precipitate increased levels of peer learning among students (OECD-CERI, 2005). Elsewhere, we have suggested that peer tutoring is a feature of the Global Studio (Bohemia and Ghassan, 2012;Ghassan and Bohemia, 2011).…”
Section: Peer Tutoring In the Global Studiomentioning
confidence: 99%